Microbiological Quality and Detection of the Genes Stx1 and Stx2 in Fresh Sausage Marketed in Tripoli, Libya - Ben Hamza I1*, Elshrek Y2, Abojnah Y2, Al gazali M3, Ibrahim K4. (AlQalam Journal of Medical and Applied Sciences, 2017)
Background: In this study, samples of fresh sausage (n=100) were collected randomly from meat shops in four different areas of Tripoli (Alhoot market, Aldhra market, Grgarsh and Alsyahia). All samples were analyzed for the presence of the following: the total aerobic plate count, Coliforms, Escherichia coli and E .coli O157:H7. The mean of total plate count for fresh sausage (Almargaz) was 2.5 x 108 CFU/g, with a range from 7 x 104 to7.5 x 109 CFU/g, with no significant differences at level (P< 0.05) between the regions of study. The mean of the most probable number of Coliforms was 1.4x103 Cell/gram (g), ranging from 1.6 x 102 to 2.4 x 103 Cell/g, indicating a significant difference at level (P< 0.01). The percentage of Escherichia coli contaminated sausage samples was 81%, with no significant differences in level (P< 0.01) between the regions of the study. The percentage of E .coli O157:H7 was contaminated sausage samples 48% with no significant differences at level (P< 0.05 ). The percentages of Stx1 gene in E. coli O157:H7 were 37.5% in the Aldhra Market, 25% in Hoot market and Grgarsh, while was 12.5% in Alsyahia. On the other hand the high percentages of Stx2 % were detected 27.5% in both Alsyahia and Grgarsh, 24.2% in Aldhra Market, while was 20.6% in the Alhoot market.